10 kW Optimization of grid-connected wind power system and its application in Xiamen. Issue 2 (March 2021) - Zhu, Guangze; li, Jiacheng; He, Zihao; Chen, Chengxiang; Zhu, Qiangqiang
Abstract: Coastal areas not only have large annual average wind speed, but also have more days of strong winds in a year. Xiamen >8 gale days, 22.4 days a year, so it is very suitable for wind power generation. This design is 10 kW wind grid-connected power generation system, each branch is composed of permanent magnet synchronous motor, rectifier, boost module, inverter and filter, 20 groups are used in parallel to form 10 kW system. Choose a single permanent magnet synchronous wind turbine power of 500 W, need 20. System DC voltage :12 V, when the power is fixed, the proper lifting of DC voltage is helpful to reduce the current, thus preventing the IGBT from causing device damage due to overcurrent. A two-dimensional fuzzy controller is used to select the outer loop error and error differential signal as input variables. In order to verify the correctness of fuzzy adaptive PI control strategy, a system simulation model is built.